Patient knowledge and acceptance of the upcoming automatic substitution of biological medicines in community pharmacies: survey of Finnish patients with inflammatory bowel disease and psoriasis - Essi Elisabeth Alanne; Emma Aarnio; Kari Linden; Johanna Timonen; Katri Hämeen-Anttila (BMC Health Services Research)
Abstract Background Automatic substitution of biological medicines in community pharmacies is among the policy measures to contain increasing pharmaceutical costs, with gradual implementation starting in Finland in 2024. It is important to study patient knowledge of biological medicines, biosimilars, and substitution, as they have an impact on the success of automatic substitution. However, there is a paucity of studies focusing on patients’ perspectives on automatic substitution in pharmacies, and the existing studies report varying patients’ opinions. Thus, the aim of the study was to (1) describe patients’ knowledge of biological medicines, biosimilars, and automatic substitution of biological medicines, (2) analyze the association of sociodemographic and health-related factors with the knowledge of biosimilars, and (3) investigate associations between knowledge, trust in pharmacists, and acceptance of automatic substitution in pharmacies. Methods An online survey was conducted in 2023 among patients aged ≥ 18 years with Crohn’s disease, ulcerative colitis, indeterminate colitis, psoriasis, pustular psoriasis, or psoriatic arthritis. Cross-tabulation, the chi-square test, and logistic regression analysis were utilized in the analysis. Results A total of 1211 participants completed the survey and were included in the analysis. Of them, 89.4% had heard of biological medicines and 43.0% of biosimilars before the survey. Biosimilar was defined correctly by 60.9%, which associated with, for example, use of original biological medicines (OR 1.57, CI 1.14–2.16) compared to being biological naïve. Of the participants, 37.3% had heard of the upcoming substitution of biological medicines in pharmacies. The upcoming substitution was considered a good reform by 38.2%. However, some participants were unsure (14.4%) or did not know enough about the topic (27.5%). The opinion whether the automatic substitution is a good reform was associated with incorrect knowledge of biosimilars. However, the trust in pharmacists’ proficiency to substitute a biological medicine was not associated with the knowledge of biosimilars. Conclusions The majority of the participants had not heard of biosimilars or the substitution of biological medicines before the survey, and furthermore, incorrect knowledge of biosimilars was associated with the opinion that automatic substitution is a good reform. Healthcare providers should prioritize patient education on biosimilars to improve acceptance of substitution.